The handbook of chlorination and alternative disinfectants - White, George Clifford. (J. Wiley, 1999)
Chlorine: history, manufacture, properties, hazards, and uses. Hypochlorination. On-site generation of Chlorine. Chemistry of Chlorination. Determination of Chlorine residuals in water and wastewater treatment. Chlorination of Potable water. Chlorination of wastewater...